A perspective on the development of gas-phase chemical mechanisms for Eulerian air quality models. (2nd January 2020) - Stockwell, William R.; Saunders, Emily; Goliff, Wendy S.; Fitzgerald, Rosa M.
ABSTRACT: An essential component of a three-dimensional air quality model is its gas-phase mechanism. We present an overview of the necessary atmospheric chemistry and a discussion of the types of mechanisms with some specific examples such as the Master Chemical Mechanism, the Carbon Bond, SAPRC and the Regional Atmospheric Chemistry Mechanism (RACM). The first versions of the Carbon Bond and SAPRC mechanisms were developed through a hierarchy of chemical species approach that relied heavily on chemical environmental chamber data. Now a new approach has been proposed where the first step is to develop a highly detailed explicit mechanism such as the Master Chemical Mechanism and the second step is to test the detailed explicit mechanism against laboratory and field data. Finally, the detailed mechanism is condensed for use in a three-dimensional air quality model. Here it is argued that the development of highly detailed explicit mechanisms is very valuable for research, but we suggest that combining the hierarchy of chemical species and the detailed explicit mechanism approaches would be better than either alone. Implication : Many gas-phase mechanisms are available for urban, regional and global air quality modeling. A "hierarchy of chemical species approach, " relying heavily on smog-chamber data was used for the development of the early series of mechanisms. Now the development of large, explicit master mechanisms that may be condensed is a significant, trend. However, a continuing problem with air quality mechanism development is due to the high complexity of atmospheric chemistry and the current availability of laboratory measurements. This problem requires a balance between completeness and speculation so that models maintain their utility for policymakers.